Quest for Ranking Excellence Impact Study of Research Metrics - Pakkan, Sheeba; Sudhakar, Christopher; Tripathi, Shubham; Rao, Mahabaleshwar (DESIDOC Journal of Library & Information Technology, 2021)
It is a general trend that higher education institutions must undergo one or more ranking agencies evaluation to get reputed in the field of education. Institutions must have a place in the ranking to attract students, faculty and even for successful foreign student exchange programs. Prominence in research is an important parameter to scale the eminence of an institution. A quantum of quality publications is one of the factors judging the prevailing research environment of an institution. While doing an institutional level evaluation on research output, we always go for quantitative measures like total publication, citation and h-index. In the present scenario, the institution must set to have a strategy in achieving ambitious scientific goals. This paper presents some innovative analysis of research data by choosing valuable metrics. The samples selected for the study are the top-ranked institutions in India. The same approach can be applied to any institutions in the world for evaluation and excellence. We have done qualitative-quantitative analysis using different parameters of research output to explain the importance of various metrics. The present study has identified metrics which can be considered seriously to achieve better performance in research output. It is a fused index metrics which explains along with Scholarly Output, the importance of Cited and Uncited Publications and different types of Collaborations and its impact on the overall performance of an institution.